The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/19476337.2019.1640797
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristic and antioxidant activity of yogurt containing olive leaf hot water extract

Abstract: The objective of this study was to determine the antioxidant and quality characteristics of yogurt containing olive leaf hot water extract (CON: 0, OLY1: 0.1, OLY2: 0.2, and OLY4: 0.4% (w/v)) stored at 4°С for 15 days. After storage, the lactic acid bacteria count showed no significant difference between yogurt samples either in the presence or absence of olive leaf extract (p > 0.05). The total phenolic content, DPPH radical scavenging activity, and reducing power increased upon increasing the content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 41 publications
18
37
0
1
Order By: Relevance
“…116 Peker and Arslan 88 investigated OLE addition in low fat apricot yogurt, thus obtaining that dry matter, protein, ash contents, pH value and Streptococcus thermophilus growth were influenced by OLE addition and especially at the highest concentration the antioxidant activity was increased with respect to the control samples. The same increase in antioxidant activity was found by Cho et al, 89 and titratable acidity, antioxidant activity, syneresis and sensory evaluation were detected to be significantly different between control and OLE samples. After storage, the lactic acid bacteria count showed no significant difference between yogurt samples either in the presence or absence of OLE, with a final count of about 8.59 to 9.14 log CFU g −1 .…”
Section: Yogurtsupporting
confidence: 83%
“…116 Peker and Arslan 88 investigated OLE addition in low fat apricot yogurt, thus obtaining that dry matter, protein, ash contents, pH value and Streptococcus thermophilus growth were influenced by OLE addition and especially at the highest concentration the antioxidant activity was increased with respect to the control samples. The same increase in antioxidant activity was found by Cho et al, 89 and titratable acidity, antioxidant activity, syneresis and sensory evaluation were detected to be significantly different between control and OLE samples. After storage, the lactic acid bacteria count showed no significant difference between yogurt samples either in the presence or absence of OLE, with a final count of about 8.59 to 9.14 log CFU g −1 .…”
Section: Yogurtsupporting
confidence: 83%
“…The abundant dietary fiber in the banana peel might be explained the high viscosity of the yogurt. Similar results were also reported by Yadav et al (2018) and Cho et al (2020). Moreover, The fortification of banana peel extract in yogurt had no significant (p > .05) difference on syneresis among the fortified and control yogurts on each analysis day ( Table 3).…”
Section: Viscosity Syneresis Lactic Acid Percentage and Ph Of Fosupporting
confidence: 86%
“…Overall, the results indicated that OLE, both added alone and together with sorbic acid, exerted an antioxidant activity in cheese. Different authors showed the antioxidant effect exerted by OLE in dairy products and according to literature the antioxidant power was lower in Ctr in a range of 40–80% and decreased during storage [ 53 , 54 ]. From this outcome it can be hypothesized that the higher presence of aldehydes in the VOC profile of OLE samples was mostly due to microbial activity rather than to fat oxidation.…”
Section: Resultsmentioning
confidence: 99%